KAJIAN TERHADAP METODOLOGI TAFSIR AL-AMANAH - Ruslan Ruslan (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2018)
This article aims to describe the methodology of the interpretation of Al-Amanah by Quraish Shihab. The method of presentation is descriptive qualitative, in the sense that the data presented is as is. Tafsir al-amanah is the forerunner to the compilation of al-Qur'an al-Karim Tafsir: Interpretation of Short Letters Based on the Revelation of Revelation. Which is the work of commentary Quraish Shihab, published in 1997 by Pustaka Hidayah in Bandung. Initially the writings that were published in the magazine Amanah. This interpretation only contains two discourse of the letter, namely surah al-‘Alaq and al-Mudatstsir. The writing style is still very simple. Tafsir al-Amanah is classified as a description of tahliliy because of its coherent description from verse to verse. In addition, this interpretation can also be called its presentation as a thematic interpretation dish, but this interpretation is not very popular compared to the work of other Quraish Shihab interpretations which are not thematic as constructed by Al-Farmawi. Al-Amanah's interpretation methodology can inspire especially those who are interested in interpreting other interpretations. In terms of methodology, Tafsir Al Amanah includes the interpretation of bi al-riwayah and bi al-dirayah. The combination of the two streams or colors of interpretation which has been known. Tafsir Al-Amanah has a detailed, detailed, in-depth and comprehensive interpretation. Key terms in each verse are analyzed by multi-analysis and the study of asbab al-nuzul is not spared as part of its interpretation method as long as the verse has asbab al-nuzul. linguistic and sociohistorical analysis.KeywordsInterpretation; methodology; al-amanah; and analysis